REPRODUCTIVE BIOLOGY AND FLORAL VISITORS OF DISTIMAKE AEGYPTIUS (CONVOLVULACEAE) IN THE CAATINGA: A COMPARATIVE STUDY - Ximenes Portela, Luís Henrique; Bezerra de Souza, Elnatan (Essentia - Revista de Cultura, Ciência e Tecnologia da UVA, 2023)
Distimake aegyptius, a native species commonly found in the Brazilian semi-arid region, has a rapid growth capacity in anthropized environments and is considered self-compatible. Considering the environmental heterogeneity of the Caatinga, we aimed to conduct a study on the reproductive system and guild of floral visitors of D. aegyptius, comparing the data found with those available for other areas of the domain. We conducted the experiments in Sobral and Frecheirinha, Ceará, between May and August 2019. We confirmed that the flowering of D. aegyptius is directly associated with the occurrence of precipitation, while its fruiting is related to the beginning of the dry season. The flowers exhibit attributes that characterize them as melitophilic with generalist pollination, being Apis mellifera, Ancyloscelis apiformis and Polybia ignobilis their effective pollinators. The guild of floral visitors differed between areas, which may be related to site conservation or competition with other species. Rates higher than 80% were recorded in manual and control cross-pollination experiments (natural conditions), indicating that the species is self-compatible and presents a reproductive strategy similar to that described for other Caatinga environments.